Psikoterapi Menurut Ilmuwan Muslim Dan Beberapa Contoh Aplikasinya - Fadhilah Fadhilah (LPPM Universitas Dharma Andalas, 2022)
There are several forms of psychotherapy or clinical intervention to help individuals or groups deal with the psychological problems they are facing according to clinical psychology. Among them are psychodynamic-oriented psychoanalysis, phenomenological and humanistic-existential, behavioral therapy, group therapy, family therapy and couples therapy, and finally philosophical and religious therapy. The last type of psychotherapy above will be the subject of discussion in this paper. Actually, philosophical and religious therapy is not new but has been around for a long time. Formerly known as pastoral therapy, which is carried out by priests in the Catholic community. In this paper, the author only tries to describe the form of psychotherapy from the perspective of Muslim scientists and examples of how to apply it when dealing with clients. This research attempts to answer the questions (1) What are the forms of psychological therapy according to some Muslim scientists? 2). What are its applications in counseling and psychotherapy? The author conducted a literature study by collecting the opinions of Muslim scientists in psychological therapy for their clients, and re-explaining examples of Islamic psychotherapy applications that are considered successful in practice.